Multiple Mechanical Complications in ST-Segment Elevation Myocardial Infarction with Angiographically Normal Coronary Arteries - Viveiros Monteiro, A (2015)
This case report discusses an unusual presentation of ST-segment elevation myocardial infarction (STEMI) with normal coronary arteries and severe mechanical complications successfully treated with surgery. An 82-year-old man presented STEMI with angiographically normal coronary arteries and no major echocardiographic alterations at discharge. At the first month follow-up, he complained of fatigue and dyspnea, and contrast echocardiography complemented by cardiac magnetic resonance imaging revealed a large left ventricular apical aneurysm with a thrombus communicating by two jets of a turbulent flow to an aneurysmatic formation of the right ventricular apex. The patient underwent a Dor procedure, which was successful. Ventricular septal defects and ventricular aneurysms are rare but devastating complications of STEMI, with almost all patients presenting multivessel coronary artery disease. Interestingly in this case, the angiographic pattern was normal.